1986
DOI: 10.2118/12123-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Cuttings Transport in Directional Wells

Abstract: Summary A large-scale study of cuttings transport in directional wells is discussed in this paper. Previous investigators used unrealistically high fluid velocities and/or short test sections where steady-state conditions had not been established. This study used a 40-ft [12.2-m] test section. Pipe rotation and eccentricity, as well as several types of drilling muds and flow regimes, were studied. Annulus angles varied from 0 to 90°, and actual drilled cuttings were used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(114 citation statements)
references
References 13 publications
8
99
1
6
Order By: Relevance
“…This was inferred to have caused by a high impact of gravity acting on the sliding bed which led to the increase in cuttings concentrations on the lower end of the annulus. At this juncture, it is pertinent to say that this research work has demonstrated credence and the observed critical angle at 60° is in consonant with that observed by Binzanti et al (2003), Brown et al (1989), Ford et al (1990), Ogunride & Dosunmu (2012), Ozbayoglu et al (2008), , Sifferman & Becker (1992) and Tomren et al (1986). Dramatically, the declining performance of the transporting fluid reversed gradually as the hole inclination angle was changed from the near horizontal to the horizontal plane (75°-90°).…”
Section: Effect Of Hole Inclination Anglesupporting
confidence: 88%
See 1 more Smart Citation
“…This was inferred to have caused by a high impact of gravity acting on the sliding bed which led to the increase in cuttings concentrations on the lower end of the annulus. At this juncture, it is pertinent to say that this research work has demonstrated credence and the observed critical angle at 60° is in consonant with that observed by Binzanti et al (2003), Brown et al (1989), Ford et al (1990), Ogunride & Dosunmu (2012), Ozbayoglu et al (2008), , Sifferman & Becker (1992) and Tomren et al (1986). Dramatically, the declining performance of the transporting fluid reversed gradually as the hole inclination angle was changed from the near horizontal to the horizontal plane (75°-90°).…”
Section: Effect Of Hole Inclination Anglesupporting
confidence: 88%
“…Parameters such as annular flow rate, rate of penetration, fluid density, effective fluid viscosity, cuttings size, cuttings density, well inclination and pipe/hole eccentricity play leading roles in cuttings transport performance of drilling fluid (Ozbayoglu et al 2004;Stan & Avram 2014). In the same vein, other factors such as fluid flow regime and pipe rotation have also been observed to have a great impact on drilled cuttings transport in vertical, deviated, and horizontal wellbores Ozbayoglu et al 2008;Rooki et al 2014;Tomren et al 1986). …”
Section: Introductionmentioning
confidence: 99%
“…Some of affective parameters on wellbore cleaning have been studied by some researchers experimentally (Tomren et al 1986;Yu et al 2004;Ford et al 1990;Hareland et al 1993;Okrajni and Azar 1986;Sifferman and Becker 1992;Hussaini and Azar 1983) and by modeling approach (Nguyen and Rahman 1998;Wazed 2002;Akhshik et al 2015;Zhu et al 2013). Tomren et al (1986) published the results of experimental studies with various drilling fluids in plastic pipe lines with inclination angle from 0° to 90°. They stated that for a constant mud flow rate cutting bed thickness increased by increasing inclination angle.…”
Section: Introductionmentioning
confidence: 99%
“…Although various affecting parameters on hole cleaning have been reported by some researchers during past decades (Tomren et al 1986;Yu et al 2004;Ford et al 1990;Hareland et al 1993;Okrajni and Azar 1986;Sifferman and Becker 1992;Hussaini and Azar 1983;Nguyen and Rahman 1998;Wazed 2002;Akhshik et al 2015;Zhu et al 2013), a comprehensive investigation of drilling fluid, cutting density, deposit ratio, string stress on the hole cleaning especially in horizontal wells has not been fully studied. Highlighting the contribution of the article, in this study various affecting parameters on hole cleaning in horizontal well by CFD simulator have been investigated and the results are verified with experimental data in literature.…”
Section: Introductionmentioning
confidence: 99%
“…This brings about effective cuttings removal as the cuttings are removed as fast as they are generated [4]. Flow rate of mud has significant positive effect on cuttings removal away from PDC bit [5][6][7][8][9]. Increasing the annular velocity by increasing the flow rate decreases the cuttings bed height significantly.…”
Section: Bit Hydraulicsmentioning
confidence: 99%